Framing anti-Americanism in Turkey: An empirical comparison of domestic and international media. (1st June 2020) - Onat, Ismail; Cubukcu, Suat; Demir, Fatih; Akca, Davut
Anti-Americanism is a growing tendency among people in Turkey, and the media is one source of this negative sentiment. After the failed military coup attempt in Turkey on 15 July 2016, more than 150 domestic media outlets were shut down, including television channels, daily newspapers, radio stations, news websites, and even social media. Local affiliates of international media companies such as Deutsche Welle Turkish, however, have remained immune to such government interventions to some extent. Considering the difference in the level of independence from Turkish government influence, this study aims to explore how the anti-American sentiment in the news varied across different media outlets. With the content of 690 online news reports, a sentiment analysis compared the pro-government Sabah and Yeni Şafak daily newspapers with two internationally owned and more independent media outlets, BBC News Turkish and Deutsche Welle. The results showed a significant discrepancy between the two groups in terms of how they framed news related to the United States. The domestic media framed and reported the US-related news with a more negative slant, including the use of offensive and pejorative narratives about the United States and its politics. BBC Turkish and Deutsche Welle, however, reported news about the United States with a relatively more neutral and objective language.